Land reform and tribal development - "Thirunavukkarasu, S." (Delhi, 2006)
This is a useful research/reference book for the researchers and policy- makers on tribal issues. The main focus of the book is on land and tribal development. The study area is unique because the tribals are the beneficiaries of the Land Reforms. This work highlights the history of the tribals and the study area for over 200 years and the resultant situation after the introduction of ryotwari system in the Hills. The Seven Chapters of this book covers all the relevant issues on the research problems. It is written in lucid style, provides systematic, succinct and appropriate analysis to make this work worthwhile.
Keywords: Tribes